The Use of YouTube-Based Short Films as Learning Media for Arabic Vocabulary Acquisition at Madrasah Tsanawiyah Laboratorium UINSU - Diva Rahima Wafda Parinduri; Salamuddin Salamuddin (Diwan Media Pustaka, 2026)
The use of digital technology in language learning has become increasingly relevant in response to evolving educational practices that require the integration of contextual and interactive learning media. In Arabic language learning, particularly in vocabulary acquisition, audiovisual media such as YouTube-based short films offer an alternative approach by integrating visual elements, audio stimuli, and authentic language contexts to provide learning experiences. This study aims to describe the implementation of YouTube-based short films as learning media for Arabic vocabulary instruction and to explore the benefits and challenges encountered during its application at Madrasah Tsanawiyah Laboratorium UINSU. This research employed a descriptive qualitative approach. Data were collected through classroom observations, interviews with teachers and students, and documentation of learning activities. The collected data were analyzed using the interactive analysis model proposed by Miles, Huberman, and Saldaña to identify emerging patterns related to media implementation. The findings reveal that YouTube-based short films serve as supplementary instructional media for Arabic vocabulary learning by providing more contextualized learning experiences, helping students understand vocabulary meanings through visual representations and conversational contexts, and increasing students' engagement throughout the learning process. This study contributes to research on digital technology-based Arabic language learning and provides insights for future studies on integrating audiovisual media into language education.